Large scale synthesis of full-color emissive carbon dots from a single carbon source by a solvent-free method - Ding, Hui; Zhou, Xuan-Xuan; Zhang, Zi-Hui; Zhao, Yun-Peng; Wei, Ji-Shi; Xiong, Huan-Ming (Nano research, 2022)
Full-color emissive carbon dots (CDs) hold a great promise for various applications, especially in light emitting diodes (LEDs). However, the existing synthetic routes for CDs are carried out in solutions, which suffer from low yields, high pressures, various byproducts, large amounts of waste solvents, and complicated photoluminescence (PL) origins. Therefore, it is necessary to explore large scale synthesis of CDs with high quantum yield (QY) across the entire visible range from a single carbon source by a solvent-free method. In this work, a series of CDs with tunable PL emission from 442 to 621 nm, QY of 23%–56%, and production yield within 34%–72%, are obtained by heating o-phenylenediamine with the catalysis of KCl. Detailed characterizations identify that, the differences between these CDs with respect to the graphitization degree, graphitic nitrogen content, and oxygen-containing functional groups, are responsible for their distinct optical properties, which can be modulated by controlling the deamination and dehydrogenation processes during reactions. Blue, green, yellow, red emissive films, and LEDs are prepared by dispersing the corresponding CDs into polyvinyl alcohol (PVA). All types of white LEDs (WLEDs) with high colorrendering- index (CRI), including warm WLEDs, standard WLEDs, and cool WLEDs, are also fabricated by mixing the red, green, and blue emissive CDs into PVA matrix by the appropriate ratios.